Prevailing role of contact guidance in intrastromal T-cell trapping in human pancreatic cancer - Hartmann, Natalie; Giese, Nathalia; Giese, Thomas; Poschke, Isabel; Offringa, Rienk; Ryschich, Eduard (Clinical cancer research, 2014)
Purpose: Pancreatic ductal adenocarcinoma (PDAC) is characterized by extensive collagen-rich stroma. T cells that infiltrate pancreatic cancers frequently become trapped in the stroma and do not contact tumor cells. Here, we aimed to analyze how chemokines and extracellular matrix (ECM) collagen interact in mediating T-cell infiltration in PDAC. - Experimental Design: T-cell distribution and ECM structure within tumors were analyzed. Chemokine concentrations in human PDAC were compared with the levels of immune cell infiltration. We assessed the influences of selected chemokines and collagen on directed and random T-cell movement using in vitro migration systems. - Results: PDAC overproduced several T-cell-active chemokines, but their levels were not correlated with intratumoral T-cell infiltration. In the absence of collagen, directed migration of activated T cells was induced by chemokines. Interestingly, collagen itself promoted high migratory activity of T cells, but completely abolished chemokine-guided movement. This effect was not altered by a β1-integrin blocking antibody. Activated T cells actively migrated in low-density collagen matrices, but migration was inhibited in dense collagen. Accordingly, T cells were heterogeneously distributed in the pancreatic cancer stroma, with the majority residing in areas of low-density collagen far from tumor clusters. - Conclusion: The excessive desmoplasia in PDAC promotes T-cell migration by contact guidance, which abrogates tumor cell-directed movement. Furthermore, dense collagen networks represent a physical barrier, additionally rearranging T-cell distribution to favor tumor stroma. These mechanisms are mainly responsible for intrastromal T-cell trapping in pancreatic cancer and may hinder the development of T-cell-based immunotherapies. Clin Cancer Res; 20(13); 3422-33. ©2014 AACR.